A glycomic approach reveals a new mycobacterial polysaccharide - Larrouy-Maumus,GJ; Gilleron,M; Skovierova,H; Zuberogoitia,S; Brenann,PJ; Puzo,G; Jackson,M; Nigou,J (Glycobiology, 2015)
Mycobacterium tuberculosis lipoarabinomannan (LAM) and biosynthetically related lipoglycans and glycans play an important role in host–pathogen interactions. Therefore, the elucidation of the complete biosynthetic pathways of these important molecules is expected to afford novel therapeutic targets. The characterization of biosynthetic enzymes and transporters involved in the formation and localization of these complex macromolecules in the bacterial cell envelope largely relies on genetic manipulation of mycobacteria and subsequent analyses of lipoglycan structural alterations. However, lipoglycans are present in relatively low amounts. Their purification to homogeneity remains tedious and time-consuming. To overcome these issues and to reduce the biomass and time required for lipoglycan purification, we report here the development of a methodology to efficiently purify lipoglycans by sodium deoxycholate–polyacrylamide gel electrophoresis. This faster purification method can be applied on a small amount of mycobacterial cells biomass (10–50 mg), resulting in tens of micrograms of purified lipoglycans. This amount of purified products was found to be sufficient to undertake structural analyses of lipoglycans and glycans carbohydrate domains by a combination of highly sensitive analytical procedures, involving cryoprobe NMR analysis of intact macromolecules and chemical degradations monitored by gas chromatography and capillary electrophoresis. This glycomic approach was successfully applied to the purification and structural characterization of a newly identified polysaccharide, structurally related to LAM, in the model fast-growing species Mycobacterium smegmatis.